CREDIT: Blockchain based trading optimization for circular credit systems accelerating green industry toward sustainable development goals 2030 - Wa Ode Rahyani Azizah Azka Har (Environmental, Social, Governance and Sustainable Business, 2025)
Background: A major challenge in modern industry is the high volume of waste ending in landfills and the limited implementation of circular economy principles, which hinder sustainable industrial development. This condition creates an urgent need for governance and incentive systems that improve waste management while providing long-term economic motivation for industrial actors. Previous studies highlight the role of circular economy models, carbon credit mechanisms, and blockchain technology in enhancing environmental performance and system transparency. Methods: This study adopts a qualitative, literature-based conceptual research approach to analyze circular economy practices, circular and carbon credit systems, and blockchain-based sustainability applications. The analysis focuses on synthesizing relevant theoretical insights to examine industrial waste challenges and evaluate the potential role of digital incentive systems. Findings: The results indicate that the proposed Circular Resource Exchange and Digital Incentive Trading (CREDIT) framework integrates blockchain-based activity recording, third-party verification, circular credit allocation, and inter-company credit trading within a unified system. These mechanisms are expected to enhance transparency and accountability while providing economic incentives for industries to adopt circular practices and support recycling-oriented ecosystems. Conclusion: Blockchain-enabled circular credit trading is a promising conceptual instrument for supporting the transition toward green industry and sustainable development. However, the framework remains exploratory and requires empirical validation through pilot implementation and further applied research. Novelty/Originality of this article: This study proposes an integrated conceptual framework that combines circular economy principles with blockchain-based digital incentive mechanisms, offering a new approach to circular credit governance, particularly in the context of developing economies.